2016
DOI: 10.1002/alr.21828
|View full text |Cite
|
Sign up to set email alerts
|

Chronic invasive fungal sinusitis: characterization and shift in management of a rare disease

Abstract: CIFS is an insidious disease often with months between symptom onset and diagnosis. It is differentiated from chronic granulomatous invasive fungal sinusitis (CGIFS) by a lack of granulomas on histopathology and an association with diabetes mellitus. Endoscopic debridement combined with long-term oral voriconazole was an effective treatment strategy in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 28 publications
4
44
0
Order By: Relevance
“…Its mortality is high even with timely diagnosis and treatment: ∽50% in the largest meta‐analysis to date . Risk factors for AIFS are related to functional and quantitative neutropenia, such as in cases of uncontrolled diabetes mellitus, hematologic malignancy (especially acute myeloid leukemia), chemotherapy, corticosteroid use, renal/liver failure, bone marrow transplantation (BMT), HIV/AIDS, or autoimmune disease …”
mentioning
confidence: 99%
“…Its mortality is high even with timely diagnosis and treatment: ∽50% in the largest meta‐analysis to date . Risk factors for AIFS are related to functional and quantitative neutropenia, such as in cases of uncontrolled diabetes mellitus, hematologic malignancy (especially acute myeloid leukemia), chemotherapy, corticosteroid use, renal/liver failure, bone marrow transplantation (BMT), HIV/AIDS, or autoimmune disease …”
mentioning
confidence: 99%
“…Panda et al reported no recurrence after 1 year of follow-up in 6 chronic invasive cases [14]. D’Anza et al also found no recurrence in a study of 6 patients with CIFRS [15]. The literature investigating the treatment of CIFRS is comprised almost exclusively of retrospective case series, and there is no consensus on the best treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic invasive fungal sinusitis (CIFS) is a rare infection that typically occurs in immunocompromised patients, but has a more indolent clinical course than its counterpart acute invasive fungal sinusitis (AIFS) 1‐4 . Similar to AIFS, in CIFS, fungi invade the mucosa of the nasal cavity or paranasal sinuses and can result in necrosis through angioinvasion.…”
mentioning
confidence: 99%
“…Importantly, CIFS also differs from chronic granulomatous invasive fungal sinusitis (CGIFS) in that there are no granulomas seen on histopathology. Further, most cases of CGIFS have been described in immunocompetent patients from the Sudan, Pakistan, and India, whereas this geographic bias has not been seen in CIFS 2,5 . However, as compared to AIFS in particular, the clinical outcomes of CIFS have been less well described.…”
mentioning
confidence: 99%